2019
DOI: 10.1021/acs.jpcc.9b07486
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Electrochemical Oxidation of One of the Identical Benzene Rings of Carbazole to 1,4-Quinone on the MWCNT Surface and Its Electrocatalytic Activity

Abstract: Carbazole-1,4-quinone is a key structural unit of naturally occurring carbazole-quinone alkaloids, for instance, 3-methyl carbazole-1,4-quinone (Murrayaquinone), that are widely used in pharmaceutics and medicine. These compounds are generally synthesized from tetrahydro ketone derivatives by multistep synthetic routes. Until now, there is no direct method reported for the partial oxidation of carbazole to carbazole-1,4-quinone by chemical, biochemical, or electrochemical reaction routes. Literature survey on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
(108 reference statements)
0
9
0
1
Order By: Relevance
“… Hemoglobin GCE/GMC/Heme-Nf − 380 30 ± 0.12 H 2 O 2 43 7. Carbazole GCE/MWCNT@Car − 215 ± 5 − 59 Hyd 44 8. Anthraquinone GCE/AQ@f-MWCNT − 285 − 58 DO, H 2 O 2 45 9.…”
Section: Introductionunclassified
“… Hemoglobin GCE/GMC/Heme-Nf − 380 30 ± 0.12 H 2 O 2 43 7. Carbazole GCE/MWCNT@Car − 215 ± 5 − 59 Hyd 44 8. Anthraquinone GCE/AQ@f-MWCNT − 285 − 58 DO, H 2 O 2 45 9.…”
Section: Introductionunclassified
“…These results highlight the paramount role of π–π stacking in the formation of the supramolecular assemblies and they also confirm that noncovalent interactions rule the adsorption process at the G/HNFQ-CPE/solution interphase. In this regard, Kumar and co-workers suggest that carbazole and multiwalled carbon nanotubes interact through π–π stacking, which represents the unique structural interaction that could lead to the experimentally observed restricted electrooxidation of the carbazole molecule leading to 1,4-quinone …”
Section: Resultsmentioning
confidence: 99%
“…25−27 GCE electrodes modified with naphthoquinone (anthraquinone) for the detection of [Ni(CN) 4 ] 2− and [Cu(CN) 3 ] 2− , has been recently reported by our group 26,27 Among other supports based on carbons materials modified with Q molecules, we can mention the exfoliated graphite functionalized with redoxactive Q, 28 which enables the electrocatalysis of ascorbic acid oxidation, and the multiwalled carbon nanotubes (MWCNTs) anchored to a glassy carbon electrode, which are able to oxidize carbazole to carbazole-mono-1,4-quinone. 29 For the latter material, it has been proposed that a strong π−π interaction occurs, given the structural compatibility of benzene rings between MWCNTs and Q molecules. In the field of energy storage, it has been demonstrated that electroactive molecules incorporated on carbon materials can significantly improve their charge storage properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Nevertheless, such a challenge has been greatly alleviated by the recent development of electrocatalysts. 46 Redox-active electrocatalysts can enable the generation of reaction intermediates at reduced potentials with improved chemo-, 47,48 regio-, 49,50 and stereo-selectivity. 51,52 Homogeneous electrocatalysts (sometimes referred as mediators) are often the first option for a variety of electroorganic reactions because of their high adaptability and selectivity.…”
Section: High-throughput Screening For Electrocatalystsmentioning
confidence: 99%